Comparison of postoperative complications between segmentectomy and lobectomy by video-assisted thoracic surgery: a multicenter study - Bédat, Benoît (J Cardiothorac Surg, 2019)
BACKGROUND: Compared to lobectomy by video-assisted thoracic surgery (VATS), segmentectomy by VATS has a potential higher risk of postoperative atelectasis and air leakage. We compared postoperative complications between these two procedures, and analyzed their risk factors. METHODS: We reviewed the records of all patients who underwent anatomical pulmonary resections by VATS from January 2014 to March 2018 in two Swiss university hospitals. All complications were reported. A logistic regression model was used to compare the risks of complications for the two interventions. Adjustment for patient characteristics was performed using a propensity score, and by including risk factors separately. RESULTS: Among 690 patients reviewed, the major indication for lung resection was primary lung cancer (86.4%) followed by metastasis resection (5.8%), benign lesion (3.9%), infection (3.2%) and emphysema (0.7%). Postoperatively, there were 80 instances (33.3%) of complications in 240 segmentectomies, and 171 instances (38.0%) of complications in 450 lobectomies (P = 0.73). After adjustment for the patient’s propensity to be treated by segmentectomy rather than lobectomy, the risks of a complication remained comparable for the two techniques (odds ratio for segmentectomy 0.91 (0.61–1.30), p = 0.59). Length of hospital stay and drainage duration were shorter after segmentectomy. On multivariate analysis, an American Society of Anesthesiologists score above 2 and a forced expiratory volume in one second below 80% of predicted value were significantly associated with the occurrence of complications. CONCLUSIONS: The rate of complications and their grade were similar between segmentectomy and lobectomy by VATS.